2003
DOI: 10.1093/jac/dkh003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high doses of liposomal amphotericin B in the treatment of experimental aspergillosis

Abstract: Infusion of L-AmB doses as high as 10 mg/kg/day may be a good therapeutic option for the management of invasive pulmonary aspergillosis developing in the context of steroid immunosuppression, although further studies are needed to assess this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…10 Several studies have suggested that a high-dose lipid formulation of amphotericin B (HD-LPD/AMB; 10 mg kg À1 per day) improves the survival rate in patients with invasive aspergillosis. [11][12][13][14][15][16] Anecdotal experience at our institution supported these studies' findings and this led to the widespread use of HD-LPD/AMB as salvage treatment for invasive aspergillosis in hematologic malignancy patients. 17 In addition, in vitro studies suggesting that the echinocandin caspofungin has synergistic activity with amphotericin B for at least half of the Aspergillus isolates tested 18 and clinical studies showing that this combination had a response rate exceeding 55% in patients with invasive aspergillosis 19,20 led to our use of HD-LPD/AMB plus caspofungin.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…10 Several studies have suggested that a high-dose lipid formulation of amphotericin B (HD-LPD/AMB; 10 mg kg À1 per day) improves the survival rate in patients with invasive aspergillosis. [11][12][13][14][15][16] Anecdotal experience at our institution supported these studies' findings and this led to the widespread use of HD-LPD/AMB as salvage treatment for invasive aspergillosis in hematologic malignancy patients. 17 In addition, in vitro studies suggesting that the echinocandin caspofungin has synergistic activity with amphotericin B for at least half of the Aspergillus isolates tested 18 and clinical studies showing that this combination had a response rate exceeding 55% in patients with invasive aspergillosis 19,20 led to our use of HD-LPD/AMB plus caspofungin.…”
Section: Introductionsupporting
confidence: 52%
“…Animal data have demonstrated that HD-LPD/AMB is associated with a higher survival rate and a significant decrease in fungal biomass compared with regular-dose conventional amphotericin B or regular-dose LPD/AMB. 11,12 Furthermore, anecdotal clinical reports have suggested that HD-LPD/AMB is safe, well tolerated and associated with a relatively high response rate (greater than 55%) in patients with invasive aspergillosis. [13][14][15][16] Walsh et al 13 reported that patients with invasive pulmonary invasive aspergillosis who received HD-LPD/AMB (X7.5 mg kg À1 per day) had an overall response rate of 71%, and Ryan et al 15 reported a 75% response rate to HD-LPD/AMB among eight patients with invasive aspergillosis who had hematologic malignancies.…”
Section: Primary Antifungal Therapymentioning
confidence: 99%
“…Data from animal models suggest that, compared with standard dose, higher doses of liposomal amphotericin (LAmB) (10 mg/kg/day) reduce the fungal burden 1 and that up-front loading doses may improve survival. 2,3 In humans, 10 mg/kg/day achieves maximum plasma concentrations and is well tolerated.…”
mentioning
confidence: 99%
“…Female Wistar rats (180 to 200 g; Harland Iberica, Spain), fed with a low-protein diet, were immunosuppressed with 125 mg of subcutaneous cortisone acetate (Sigma Chemical Co., St. Louis, MO) per kg of body weight three times per week, from 14 days before infection to the end of the experiment (11).…”
mentioning
confidence: 99%
“…Conidia were counted in a hemocytometer and adjusted to 8 ϫ 10 6 cells/ml in sterile saline. Intravenous treatments were administered through a central venous catheter (11). Aerosols were generated by a CR60 compressor (Medic-Aid Ltd., West Sussex, United Kingdom; flow rate, 10 liter/min) attached to a Nebulizer II Oxinova (Carburos Metálicos, Barcelona, Spain) and were led through a nose-only exposure inhalation chamber (Panlab, Spain) over a 60-min period.…”
mentioning
confidence: 99%